Assembling Reading and Writing in the Face of Loss: Christa Couture’s How to Lose Everything and Dakshana Bascaramurty’s This Is Not the End of Me - Lola Artacho-Martín (Canada and Beyond)
Through nonfictional texts dealing with complicated and traumatic experiences related to loss, readers and writers seem to become more intricately entangled. Following Rita Felski, reading is said to ignite a process of “recognition” (23) which might be paralleled to the self-discovery process which writing may achieve. Sympathy and mutual identification arise and bring readers’ and writers’ identities closer, creating an intersubjective space where health and illness assemble their relations. This analysis of Christa Couture’s How to Lose Everything and Dakshana Bascaramurty’s This is Not the End of Me: Lessons on Living from a Dying Man will attempt to show that there is a tight link between reader and writer through nonfiction which transcends the literary text. In addition, the healing nature of this connection will be highlighted, which supports the idea of using reading and writing techniques as therapeutical strategies in the coping with emotional turmoil and distress.